Controllable Direction of Porphyrin Derivatives in Two Cyclodextrin Cavities. Issue 18 (11th May 2018) - Horiguchi, Banri; Nakaya, Toshimi; Ueda, Masafumi; Sugikawa, Kouta; Mizuta, Tsutomu; Haino, Takeharu; Kawata, Naomi; Ikeda, Atsushi
Abstract : Porphyrin–trimethyl‐β‐cyclodextrin (TMe‐β‐CDx) complexes have pseudorotaxane structures in which two meso ‐phenyl and/or ‐pyridyl moieties penetrate the upper rim of two TMe‐β‐CDx molecules. Porphyrin derivatives with one to three pyridyl moieties at meso positions formed complexes with TMe‐β‐CDx in which the penetration of the upper rim of the two TMe‐β‐CDxs by the pyridyl moieties was minimized. In contrast, in TMe‐β‐CDx complexes formed with porphyrin derivatives bearing two 2‐methoxyphenyl moieties and two pyridyl moieties, the pyridyl moieties penetrate the upper rim of the two molecules because steric hindrance prevents penetration by the 2‐methoxyphenyl moieties. Abstract : meso ‐Phenyl‐ and/or ‐pyridyl‐substituted porphyrin–trimethyl‐β‐cyclodextrin (TMe‐β‐CDx) complexes have pseudorotaxane structures in which two meso ‐phenyl and/or ‐pyridyl moieties penetrate the upper rim of the two TMe‐β‐CDx molecules. Whether phenyl or pyridyl moieties penetrate the upper ring depends on the electrostatic and steric effects of the substituents.